PERBAIKAN DAYA SAING PERUSAHAAN MELALUI SISTEM PENGUKURAN KINERJA TERINTEGRASI: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR - Sukwadi, Ronald (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Organizational performance has always exerted considerable influence on the strategy formulation of a company. Consequently, the ways and means of accurately measuring this performance is perceived as being an increasingly important field of study for both organizations and academics alike. In order to provide an overall view of company performance, researchers have tried to combine more than one aspect of performance through the integrated performance measurement system (IPMS). In this paper, the design and analysis of this measurement system is demonstrated through an empirical study example at a metal company. The paper starts off with choosing business level in the area of performance measurement. It then goes on to specify a set of requirements of both internal and external stakeholders which performance systems should address. The requirements which are developed based on the IPMS, can be used to identify and specify key performance indicators (KPIs) of each stakeholder. Finally, the actual score of each performance measurement can be determined, and areas for future improvement are suggested.